Community Empowerment in Prevention and Management of Hypertension: Literature Review - Marni, Marni; Soares, Domingos; Firdaus, Insanul; Nurjanah, Ananda Tri; Eflin, Maria Fransisca; Husna, Putri Halimu (Global Health Science Group, 2024)
Hypertension (HT) is a significant public health concern globally, particularly in low- and middle-income countries (LMICs). It is a major contributor to cardiovascular diseases (CVDs) and requires effective prevention and management strategies. Globally, hypertension affects approximately 1.28 billion adults aged 30-79 years and in Indonesia recent studies indicating that about 34.1% of the adult population is affected, yet many remain undiagnosed or untreated.Method : This study aimed to systematically evaluate the existing evidence on community empowerment strategies in the prevention and management of hypertension. Search Strategy was used PubMed, MEDLINE, Google Scholar, and Web of Science data base. Inclusion Criteria: Studies focusing on community-based interventions. Data were extracted from the selected studies using a standardized form are: Author(s), year of publication, Study design, quality Assessment tools. For randomized controlled trials, the Cochrane Risk of Bias Tool was utilized, while observational studies were evaluated using the Newcastle-Ottawa Scale. A narrative synthesis was employed to summarize the findings. Key themes regarding community empowerment strategies: Educational campaigns, workshops, Peer support, Integration with local healthcare systems, Lifestyle modification. Result : The findings revealed a significant increase in public knowledge regarding hypertension prevention after the interventions were implemented (p = 0.03). The empowering local health workers can enhance community health initiatives.Conclusion : Integration with public health systems and capacitating community health officers are also crucial for widespread adoption and cost-effectiveness. Community empowerment can lead to improved health outcomes by reducing disparities and increasing social justice.